Factors influencing the use of non-plastic reusable shopping bags: a cognitive-normative-habitual approach - Muposhi, Asphat; Mpinganjira, Mercy; Wait, Marius (Cambridge University Press, 2022)
The widespread use and irresponsible disposal of single-use plastic shopping bags are posing a significant threat to environmental sustainability. The use of non-plastic reusable shopping bags (NPRSBs) is being promoted in several jurisdictions to avert this challenge. However, this form of pro-environmental behaviour is failing to embed among consumers in emerging markets. This study therefore examines the factors influencing the behaviour of using NPRSBs among consumers, using a modified theory of planned behaviour. Data were collected from 487 South African consumers using a structured questionnaire and were analysed using structural equation modelling. The results identified ‘attitudes’ and ‘personal norms’ as the building blocks for the formation of pro-reusable shopping bags use intentions, which, in turn, influence actual behaviour. The findings also pointed to the need to foster the development of descriptive norms related to the use of NPRSBs in order to enhance mainstream use. Accordingly, this study recommends the use of rational and norm-based strategies to stimulate the behaviour of using NPRSBs.